A 1500-year paleolimnological record from an ancient debris avalanche landscape in west central Costa Rica - Horn, Sally P. (2026)
We analyzed physical properties, diatoms, and geochemistry in a 1500-year sediment profile from a small, mid-elevation lake in west central Costa Rica formed by a landslide. Laguna Arancibia occupies an area long affected by landslides, including large debris avalanches; in 2000 CE one of the largest debris avalanches recorded in Costa Rica passed within 300 m of the lake. A systematic archaeological survey provides context for the paleolimnological study, showing sparse human settlement during the Pavas archaeological phase (2250–1650 cal yr BP), a hiatus during the Curridabat phase (1650–950 cal yr BP), and repopulation during the Cartago phase (950–400 cal yr BP). Our record begins during the hiatus, when diatoms indicate a shallow lake. A major shift in diatoms followed by increased inorganic sedimentation suggests humans returned about 880 cal yr BP. Peaks in inorganic sediment influx during the Cartago phase document erosion from agricultural fields or landslides possibly triggered by forest clearance. However, stable carbon isotopes in n-alkanes of terrestrial leaf waxes indicate extensive C3 forest since reoccupation, suggesting only moderate deforestation for agriculture by a small population. The Spanish Conquest may have further reduced, or completely destroyed, this population, but evidence in the sediment record is inconclusive.